Paper-based devices as a new tool for rapid and on-site monitoring of "superbugs" - Li, Wenliang; Coulon, Frederic; Singer, Andrew; Zhu, Yong-Guan; Yang, Zhugen (American Chemical Society, 2021)
Infectious diseases are currently a significant cause of morbidity and mortality, with approximately 700 000 deaths each year worldwide.(1) Viruses, bacteria, and fungi have become increasingly resistant to antimicrobial agents, making antimicrobial resistance (AMR) one of the biggest global health challenges humanity has had to face. Recent reports have highlighted the role pandemics may play in exacerbating AMR through the increased use of disinfectants, alcohol-based hand sanitizers, and antiseptic hand wash.(2) Evidence of antibiotic mis-prescribing in hospitalised COVID-19 patients has also been reported, asking a pandemic-induced spike in AMR. Ultimately, the fate of antimicrobial agents and resulting resistant microorganisms is they are discarded into wastewater, entering the environment as sewage, sludge, and treated wastewater. This results in opportunities for further mutation and horizontal gene transfer (HGT).
Keywords: Colorimetry; Diagnostic imaging; Genetics; Bacteria; Antimicrobial agents